HUBUNGAN PENGETAHUAN DENGAN PERILAKU SADARI SEBAGAI DETEKSI DINI KANKER PAYUDARA - Sari, Reni Puspita (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
The highest cancer of Indonesianâ€™s women is breast cancer. The issue of breast cancer become larger because more than 70% of patients come to the doctor in advanced stage. Early detection of breast cancer symptoms is very important. The main purpose of early detection of breast cancer is to find the cancer in the early stages (level I), so the treatment becomes easier (Putra, 2015). Breast self examination is a simple filtering technique, and not expensive, but it is very effective to know the existence of cancer in early stage. Breast self examination should be done every month by women more than 20 years old. The aims of this research is to know the correlation between knowledge and breast self examination behavior as early detection of breast cancer. The type of this research is observational analytic research with cross sectional approach. Total population of 69 people, then the sampling done by the total sample that meets the inclusion and exclusion criteria to 67 people student of Midwifery Academy of Yayasan RS Jakarta. Instrument research using questionnaires. Data analysis technique using the Spearman's rank. Conclusion: there is a positive and significant relationship between knowledge with behavior realize as early detection of breast cancer correlation coefficients of Ï€ = 0.674 with significance level of 0.00 (P < 0.05). Â  Keywords: Knowledge, Breast self examination, Breast cancer